O adoecimento dos trabalhadores de frigorífico de frangos - Ruschel, Mariele Stertz (2017)
The purpose of this dissertation is to study the relationship of the work process and sickness of workers in chicken slaughterhouses in the municipality of Dois Vizinhos - PR. With theoretical references of Marx's social theory, it was sought to understand and explain work and work processes, as well as to define concepts, especially those related to work medicine and worker's health, which considered the historical passage through the approach of the occupational health. The general objective was to analyze the relationship between work and sickness of the workers in the Dois Vizinhos - PR agroindustry; and the specific objectives: to identify what drives the workers to leave by the sickness of their jobs in the agro industry of Dois Vizinhos - PR; and to identify and analyze how the searches are carried out for facing the sickness by workers, such as access to treatment of the disease, their approval in medical expertise with the social security institution and their subsequent rehabilitation to work. Quantitative and qualitative methodological procedures were adopted when interviews were carried out with workers away from their workplaces. The criterion for selecting the interviewees left without worrying about the disease that led to their departure from the workplace. Other interviews were conducted with trade union leaders and scholars, aiming to deepen aspects related to the object of studies. Secondary sources of research were also verified to obtain data from state institutions, such as the INSS and also to characterize the cold storage company. Blood, feces, dust, excessively cold environments and extremely cold, are characteristic of place where peoplework fridge. Work the chicken refrigerator, which requires compliance with phytosanitary standards, are closed, with few windows, artificial refrigeration and maintenance of the ambient temperature necessary for the satisfaction of the production and not of the working humans. The work in the cold store is organized in production shifts (morning, afternoon and evening) and the production lines determine the speed, the rhythms of the movements and the attention given by the workers. In the capitalist mode of production, labor distances itself from its ontological perspective, focusing on processes that resemble social being in the production of other commodities aimed at accumulation. In contemporary times, due to the flexibilization of the forms of production and labor contracts, the pace of production increases the suffering and physical and mental illness of the workers, which is accompanied by the loss of labor rights and social security. It was confirmed what previous studies have done, that the diseases of the workers, even if individualized, are directly related to the production and work process adopted by the refrigerator. They have been deciphered the mechanisms they have followed, in the consequences arising from the processes of withdrawal from work due to illness, such as the suspension of benefits, long periods without salary, being subjected to examinations and searches for a causal link between illness and work of experts, have health care pantries.